ASUHAN KEBIDANAN BERKELANJUTAN (Continuty Of Care) DENGAN EMESIS GRAVIDARUM - Erna Yuliana; Mei Lia Nindya Zulis Windyarti (Politeknik Unggulan Kalimantan, 2022)
Background: The most important indicators that determine public health status are maternal mortality (MMR) and infant mortality (IMR). In reducing MMR and IMR, a midwife has a very important role. Providing care during pregnancy, childbirth, neonates and the puerperium is the role of the midwife in ongoing examinations. Methods: Descriptive observational case study approach. Results: During the pregnancy, Mrs. A had 6 visits and during the first trimester, Mrs. A had experienced emesis gravidarum. Therefore, the authors provide non-pharmacological therapy PC 6 Acupressure because it is beneficial to increase the release of beta endorphins in the pituitary around the CTZ. Beta endorphin is a type of endogenous antiemetic that can cause inhibition of nausea and vomiting impulses in the vomiting center and CTZ. During the third trimester, Mrs. A had experienced back pain. Then the authors provide non-pharmacological therapy to the form of effleurage massage to provide a sense of comfort, relaxation, and stimulate the production of endorphins hormones that can naturally divert the pain. The birth process went smoothly and took place spontaneously. In addition, the care of the newborn and the postpartum period were all within normal limits. Conclusion: Continual midwifery care is provided, in accordance with the results of existing theories.